Empowering Employability: LP3I Polytechnic Students' Perceptions of English CV Development in ESP I - Kurniadi, Yudi; Untung Eko Setyasari; Lutfi Kausar Rahman (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
Understanding job vacancy advertisement material, making English CV, and cover letters in ESP I learning are some of the steps to prepare students for English job interview practice material as well as provisions when students are looking for work. Making an English CV in ESP I learning is a useful thing for students because students learn to compile an English CV starting from personal statement, objective, skills, experience to achievement. In addition, students learn to understand word and sentence structure, use adjectives, check spelling, and use several action verbs. Therefore, the writer tries to find out how students perceive the making of an English CV in ESP1 learning, where the English CV contains various aspects that must be mastered by students. The research method used is quantitative and qualitative research methods (mixed method) by obtaining data through questionnaires and interviews with respondents, namely several LP3I Polytechnic students of Tasikmalaya Campus. The results of this study reveal that making an English CV in ESPI learning can provide convenience and usefulness for students. Therefore, it can be concluded that making an English CV in ESP1 learning can help students in producing clear and structured English CV work so that by making an English CV it can facilitate students in practicing English job interviews and at the same time as a provision for students to apply for jobs in real life.